2009
DOI: 10.2176/nmc.49.542
|View full text |Cite
|
Sign up to set email alerts
|

Primary Epidural Peripheral Primitive Neuroectodermal Tumor of the Thoracic Spine -Case Report-

Abstract: A 25-year-old male patient presented with an extremely rare primary spinal peripheral primitive neuroectodermal tumor (pPNET) manifesting as acutely progressive paraparesis and back pain. Neuroimaging and intraoperative examination showed that the tumor was confined to the epidural space of the thoracic spine. The patient was treated successfully by gross total resection of the tumor followed by chemotherapy and local radiotherapy. The present case illustrates the unexpected occurrence and important differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…After reviewing literatures, the authors concluded that no evidence was shown that craniospinal axis radiation was more effective than local radiation, and cisplatin-based combination chemotherapy may be the first-line treatment in recurrent or refractory Ewing sarcoma tumors. [ 12 ] In a case report with literature review, Sharma et al concluded that maximal safe resection followed by aggressive chemoRT appeared to be the standard treatment. In this study, they also mentioned that because RT could be detrimental to the spinal cord, especially in the pediatric age group, intensity-modulated radiation, and proton beam RT have received attention, which are known to have better dose distribution.…”
Section: Discussionmentioning
confidence: 99%
“…After reviewing literatures, the authors concluded that no evidence was shown that craniospinal axis radiation was more effective than local radiation, and cisplatin-based combination chemotherapy may be the first-line treatment in recurrent or refractory Ewing sarcoma tumors. [ 12 ] In a case report with literature review, Sharma et al concluded that maximal safe resection followed by aggressive chemoRT appeared to be the standard treatment. In this study, they also mentioned that because RT could be detrimental to the spinal cord, especially in the pediatric age group, intensity-modulated radiation, and proton beam RT have received attention, which are known to have better dose distribution.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of primitive neuro ectodermal tumour to disseminate along the neuraxis supports prophylactic craniospinal irradiation with an involved boost to the primary site. 7-9 …”
Section: Discussionmentioning
confidence: 99%
“…Bazı yazarlar ekstradural bölgeye sınırlı, kraniyospinal yayılımı olmayan olgularda lokal radyoterapinin yeterli olabileceğini bildirmişlerdir. [17] Radyoterapi sahası ile birlikte radyoterapi dozu da tartışmalıdır. Albrecht ve ark.…”
Section: Discussionunclassified